2012
DOI: 10.1016/j.jom.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Reducing uncertainty in supplier selection decisions: Antecedents and outcomes of procedural rationality

Abstract: a b s t r a c tSupplier selection decisions are characterized by a high degree of uncertainty. We draw upon the behavioral operations management and decision-making literatures to examine factors that lead to the adoption of procedural rationality as a decision strategy. In addition, we emphasize the effect of procedural rationality on decision-makers' perceived uncertainty and subsequent supplier decision performance. Our structural equation model with cross-country survey data from 461 respondents in the Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 142 publications
(191 reference statements)
3
77
0
2
Order By: Relevance
“…Ellis et al (2010) found that high supply disruption risk perceptions lead toward behavior that seeks new supply sources. Similarly, we view a high level of perceived risk as prevalent in supplier selection decisions because of the uncertainty associated with predicting selected suppliers' performance (Talluri, Narasimhan, & Nair, 2006;Wouters, Anderson, Narus, & Wynstra, 2009;Riedl, Kaufmann, Zimmermann, & Perols, 2013). As agents of the firm, supply managers are tasked with protecting the firm's competitive position (Zsidisin & Ellram, 2003;Fiegenbaum & Thomas, 2004).…”
Section: Influences On Supplier Selection Risk Takingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ellis et al (2010) found that high supply disruption risk perceptions lead toward behavior that seeks new supply sources. Similarly, we view a high level of perceived risk as prevalent in supplier selection decisions because of the uncertainty associated with predicting selected suppliers' performance (Talluri, Narasimhan, & Nair, 2006;Wouters, Anderson, Narus, & Wynstra, 2009;Riedl, Kaufmann, Zimmermann, & Perols, 2013). As agents of the firm, supply managers are tasked with protecting the firm's competitive position (Zsidisin & Ellram, 2003;Fiegenbaum & Thomas, 2004).…”
Section: Influences On Supplier Selection Risk Takingmentioning
confidence: 99%
“…Experience is especially important as individuals' behavior toward risk can change over time (Sitkin & Weingart, 1995). Previous studies note the importance of experience because decision-makers draw from past successful decision strategies (Beach & Mitchell, 1978;Riedl et al, 2013).…”
Section: Control and Validation Variablesmentioning
confidence: 99%
“…Mantel et al (2006) revealed that make-or-buy evaluations were influenced by environmental factors such as the vividness of the information and perceived risk. Riedl et al (2013) also argued that organizational, situational, and personal characteristics influence the extent of rationality in supplier selection. Furthermore, their study found some differences in the effects of those characteristics between two countries.…”
Section: Behavioral Studies In Purchasing and Supply Managementmentioning
confidence: 99%
“…This type of research would likely further develop and expand current operations management research on the various forms of uncertainty entrepreneurs and entrepreneurial firms face in the new product development process (e.g., market, creative, and process uncertainty [Anderson & Joglekar, 2005]) and methods to handle these uncertainties, including, for example, flexible manufacturing capacity (Fine & Freund, 1990), trial-and-error learning or real options reasoning (Sommer & Loch, 2004), supplier selection (Riedl, Kaufmann, Zimmermann, & Perols, 2013;Simangunsong, Hendry, & Stevenson, 2016), and maybe even supply chain management (Seshadri & Subrahmanyam, 2005;Tomlin, 2003).…”
Section: Operations Management Of Opportunity Identification and Evalmentioning
confidence: 99%